The rock abrasion record at Gale Crater: Mars Science Laboratory results from Bradbury Landing to Rocknest. Issue 6 (18th June 2014) - Bridges, N. T.; Calef, F. J.; Hallet, B.; Herkenhoff, K. E.; Lanza, N. L.; Le Mouélic, S.; Newman, C. E.; Blaney, D. L.; de Pablo, M. A.; Kocurek, G. A.; Langevin, Y.; Lewis, K. W.; et al.
Abstract: Ventifacts, rocks abraded by wind‐borne particles, are found in Gale Crater, Mars. In the eastward drive from "Bradbury Landing" to "Rocknest, " they account for about half of the float and outcrop seen by Curiosity's cameras. Many are faceted and exhibit abrasion textures found at a range of scales, from submillimeter lineations to centimeter‐scale facets, scallops, flutes, and grooves. The drive path geometry in the first 100 sols of the mission emphasized the identification of abrasion facets and textures formed by westerly flow. This upwind direction is inconsistent with predictions based on models and the orientation of regional dunes, suggesting that these ventifact features formed from very rare high‐speed winds. The absence of active sand and evidence for deflation in the area indicates that most of the ventifacts are fossil features experiencing little abrasion today. Key Points: Ventifacts in Gale Crater May be formed by paleowind Can see abrasion textures at range of scales